2016
DOI: 10.1007/s00449-016-1588-7
|View full text |Cite
|
Sign up to set email alerts
|

Predictive functional profiling using marker gene sequences and community diversity analyses of microbes in full-scale anaerobic sludge digesters

Abstract: Anaerobic digestion (AD) is widely used in treating the sewage sludge, as it can reduce the amount of sludge, eliminate pathogens and produce biofuel. To enhance the operational performance and stability of anaerobic bioreactors, operational and conventional chemical data from full-scale sludge anaerobic digesters were collected over a 2-year period and summarized, and the microbial community diversity of the sludge sample was investigated at various stages of the AD process. For the purpose of distinguishing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
16
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(26 citation statements)
references
References 52 publications
10
16
0
Order By: Relevance
“…The Euryarchaeota belonging to the Methanobacteriales, the Methanomicrobiales, the Methanosarcinales, and Thermoplasmatales were the main Archaea found out in the WWTP of Marrakech (Figure 1). The abundance of Archaea in anaerobic digesters was in concordance to those of previous studies [61,64,65] showed that Archaea was among the most abundant phyla in anaerobic digesters. The dissecting microbial community structure and methane-producing pathways, Methanobacteriales, Methanococcales, Methanomicrobiales, Methanosarcinales, and Methanopyrales were revealed to be present in a full-scale anaerobic reactor digesting activated sludge from wastewater treatment [64].…”
Section: Discussionsupporting
confidence: 91%
“…The Euryarchaeota belonging to the Methanobacteriales, the Methanomicrobiales, the Methanosarcinales, and Thermoplasmatales were the main Archaea found out in the WWTP of Marrakech (Figure 1). The abundance of Archaea in anaerobic digesters was in concordance to those of previous studies [61,64,65] showed that Archaea was among the most abundant phyla in anaerobic digesters. The dissecting microbial community structure and methane-producing pathways, Methanobacteriales, Methanococcales, Methanomicrobiales, Methanosarcinales, and Methanopyrales were revealed to be present in a full-scale anaerobic reactor digesting activated sludge from wastewater treatment [64].…”
Section: Discussionsupporting
confidence: 91%
“…The decreased Bacteroidete bacterium in animals contribute to diarrhea. Anaerotruncus can utilize cheese whey to produce acetic and butyric acids [68]. The decreased Anaerotruncus sp.…”
Section: Discussionmentioning
confidence: 99%
“… 62 , 63 “Carbohydrate metabolism” involves a complex series of enzymatic steps to convert external substrate into metabolic precursors, such as acetyl-CoA, pyruvate, and d -fructose-6-phosphate, and it involves a hydrolysis reaction in which polymers are hydrolyzed to monomers. 64 , 65 The “membrane transport” pathway involves an efflux of the irritant metals outside the cell by transporters, transformation of the metals into non-toxic/less toxic forms, and biosorption. Often, biosorption and enzymatic conversion of metal into another form occur at the same time; a metal may be absorbed into the cell, which precipitate the metal as salt.…”
Section: Discussionmentioning
confidence: 99%